Compositional multivariate statistical analysis of the hydrogeochemical processes in a fractured massif: La Línea tunnel project, Colombia. (August 2018) - Piña, Adriana; Donado, Leonardo David; Blake, Sarah; Cramer, Thomas
Abstract: Hydrogeochemical and isotopic data were used to improve the understanding of 1) Groundwater flow in a complex fractured aquifer system, 2) Surface water – groundwater interactions, and 3) Groundwater evolution within the La Línea Massif in the Cordillera Central of the Colombian Andes, using two roadway tunnels drilled there as a natural laboratory. The La Línea Massif is a crystalline structure formed by two igneous-metamorphic fractured complexes (Cajamarca Group and Quebradagrande Group), plus andesitic porphyry rocks from the Cenozoic period. The tunnels traverse eight main fault zones, where higher infiltrations of groundwater into the tunnels were reported. Water samples were collected at the surface and within the tunnels in three different sampling rounds in 2010, 2014 and 2015. Major ion concentrations and δ 18 O and δ 2 H stable isotopic ratios were measured. This database is a unique opportunity to investigate water-rock interaction processes through time in a dewatering crystalline rock massif in such an important area in the Colombian Andes. Compositional data analysis (CoDa) techniques were implemented on the major ion data before a multivariate statistical analysis (MSA). The MSA included a compositional principal component analysis (PCA) and a compositional hierarchical cluster analysis (HCA), combined with more classical graphical methods for the classification of water chemistry data, such as Piper and Stiff diagrams. According to the compositional HCA and PCA, the obtained components and clusters are first related to the location of the samples (surface or tunnel samples) followed by the geochemical processes. The geochemical variability of the massif is associated with the weathering of silicates and pyrite oxidation that generates carbonate dissolution as a result of the drainage caused by the tunnels. A temporal evolution characterized by a decrease in pH, conductivity and Mg 2+ concentrations was observed. The analysis of the stable isotopes, 2 H and 18 O, suggests that the sampled groundwater has a common origin: recharge waters with specific signatures for the east and west watersheds that exhibit alterations due to hydration because of the dissolution of plagioclases and rock-water interactions with materials exposed to hydrothermal fluids. Highlights: Hydrogeochemical and isotopic research of groundwater inflows in a tunnel. Analysis of the geochemistry evolution in time and space through a fractured massif. Use of CoDa techniques prior to a MSA to improve statistical analysis. Conceptual hydrogeological model of the La Línea Massif in Colombia.